(untitled) (Heritage, 2021)
Anarchy, which had occupied Ottoman’s Empire in its last decade, had a negative impact on the position of Serbian population. Porte did not take more decisive measures to improve the situation in the field, but their politics was founded on the favouring of Albanians. Such attitude of Turkish authorities had long-lasting consequences, and Albanian unbridleness was getting larger. Oppressions were committed every day, and the main objective of Albanians was to break off compact settlements inhabited by Serbs as it was Ibarski Kolašin. Being found between Albanian oppressors from one side, and non-interested Turkish authorities, Serbs started arming themselves more actively. They purchased rifles in Serbia, and were given assistance by their compatriots, who escaping from villains, inhabited territory in the area of the Kingdom of Serbia along the border. Besides them, they were getting to weapon via some Albanians, with a certain monetary compensation. Albanians, after knowing that Serbs are being armed from Serbia, hoped more actively of their destruction. They requested from Turkish authority’s weapon investigation in Ibarski Kolašin, and after the search of Shemsi pasha, in January of 1901 they were not pleased. In the summer of the same year, Isa Boljetinac with the help of his partisans was searching for weapon through Kolašin’s villages, by committing crimes over innocent people. During the stay of Isa Boljetini in these areas the Kolašin’s region had been deserted, and not only men were on strike but women and children as well. The only salvation from Isa’s atrocities at that moment was the presence of Russian consul Mashkov, who, by the intervention via his embassy in Constantinople, managed to obtain the publication of imperial decree on the breaking of the weapon search. The publication of imperial decree and d the retreat of Isa Boljetinac from Ibarski Kolašin did not bring peace to Serbs. Namely, Isa was not pleased with the booty he had got during the summer of 1901 so that he was persuading other Albanian villains to go on with the weapon search in Kolašin’s region.